Increases in Soil Aggregation Following Phosphorus Additions in a Tropical Premontane Forest are Not Driven by Root and Arbuscular Mycorrhizal Fungal Abundances - Camenzind, Tessa; Papathanasiou, Helena J.; Förster, Antje; Dietrich, Karla; Hertel, Dietrich; Homeier, Jürgen; Oelmann, Yvonne; Olsson, Pål A.; Suárez, Juan P.; Rillig, Matthias C. (Frontiers in Earth Science, 2016)
Tropical ecosystems have an important role in global change scenarios, in part because they serve as a large terrestrial carbon pool. Carbon protection is mediated by soil aggregation processes, whereby biotic and abiotic factors influence the formation and stability of aggregates. Nutrient additions may affect soil structure indirectly by simultaneous shifts in biotic factors, mainly roots, and fungal hyphae, but also via impacts on abiotic soil properties. Here, we tested the hypothesis that soil aggregation will be affected by nutrient additions primarily via changes in arbuscular mycorrhizal fungal (AMF) hyphae and root length in a pristine tropical forest system. Therefore, the percentage of water-stable macroaggregates (> 250 μm) (WSA) and the soil mean weight diameter (MWD) was analyzed, as well as nutrient contents, pH, root length, and AMF abundance. Phosphorus additions significantly increased the amount of WSA, which was consistent across two different sampling times. Despite a positive effect of phosphorus additions on extra-radical AMF biomass, no relationship between WSA and extra-radical AMF nor roots was revealed by regression analyses, contrary to the proposed hypothesis. These findings emphasize the importance of analyzing soil structure in understudied tropical systems, since it might be affected by increasing nutrient deposition expected in the future.